Analysis of Sharia Financial Behavior Towards the Welfare of Fishermen's Households in Berandan Kab. Langkat - Azra Nurwansyah; , Nurul JannahNurul Jannah; , Waizul Qarni (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study examines the effect of Islamic financial behavior on the welfare of fishing households in Berandan through a qualitative case study approach. The results show that 90% of fishermen have savings of less than Rp500,000 due to unstable income (Rp1-4 million/month) influenced by the season and fluctuations in fish prices, with 60% relying on high-interest loans during lean periods. Although 80% of respondents are not accustomed to structured financial record-keeping and 55% lack understanding of Islamic finance terminology, 70% expressed interest in profit-sharing systems after receiving explanations, while 85% remain consistent in paying zakat/alms as a form of spiritual resilience. These findings recommend three integrated solutions: (1) practical Islamic finance training based on concrete examples, (2) the establishment of a BMT specifically for fishermen with Islamic financing products, and (3) a sustainable mentoring program by religious leaders, which is expected to increase the financial capacity of fishermen's households by 40-60% in two years while strengthening the principles of maqasid syariah in the economic life of coastal communities.